EFFECT OF CHANNA MICROPELTES IN THE GRANULATION, FIBROSIS AND NECROSIS OF DIABETIC WOUND HEALING - Amy Nindia Carabelly; Juliyatin Putri Utami; Didit Aspriyanto; Muhammad Hasanu Reksi; Dewi Puspitasari; Priyawan Rachmadi (FKG Unlam, 2021)
Background: Diabetes mellitus (DM) is characterized by persistent hyperglycemia. The symptoms of DM is delayed wound healing. Delayed wound healing in diabetes will increase the risk of wound complications that will hinder the healing process, and lead to complications such as fibrosis and necrosis. The use of Channa Micropeltes (CM) extract at a dose of 16 mL/kg BW orally is proven to general optimal wound closure and wound contraction clinically in Wistar rats as diabetic model on day 14.However, the histopathological description of wound healing is yet to be known. Objective: To analyze the effect of 16 mL/kg BW dose of CM extract on histopathological changes of wound healing granulation tissue, fibrosis and necrosis in diabetic Wistar rats on day 14. Materials and Methods: This study was a true experimental design with a post-test only control group design. The samples were divided into two groups, namely the diabetic model group given CM extract at 16 mL/kg BW dose for 14 days, and the diabetic model group given BR2 feed only for 14 days. Results: The results of Mann-Whitney U test showed p = 0.003 for granulation tissue, p = 0.411 for fibrosis and p = 1 for necrosis, with the level of significance was p<0.05. Conclusion: The CM extract at 16 mL/kg BW dose affects the histopathological description of granulation tissue which presents a better result than those in the control group but did not affect the features of fibrosis and necrosis in diabetic Wistar rats on day 14. Keywords: Channa Micropeltes, Diabetic wound, Fibrosis, Granulation tissue, Necrosis.